Jigsaw cooperative learning strategy based lesson study on Indonesian college study in National Information Polytechnic - Husni Bt Salam (CV Rezki Media, 2020)
Indonesian language courses are compulsory subjects in every tertiary institution so a learning model is needed. The purpose of this study is to describe the Lesson Study-based cooperative learning model in the Indonesian language course at the National Informatics Polytechnic. This research was conducted in 2 cycles. The subjects in this study were 16 students of Business Administration class. The research instrument consisted of the Lesson Study feasibility study instrument sheet, the observation sheet of problem solving skills assessment and the cognitive assessment assessment sheet. The results of the study used a Lesson Study-based jigsaw method of 90%. The application of the Jigsaw model based on Lesson Study was able to improve student collaborative skills by 8.26% and cognitive learning outcomes by 1.56% from cycle I to cycle II. The conclusion of this research is a strategy using the Jigsaw model based on Lesson Study can improve the collaborative skills and cognitive learning outcomes of each student.